Students’ awareness on the use of digital library in tertiary institutions in Ekiti state for sustainable development - Adepoju, Eunice Olayinka; Sunday, Ogunmodede Aderemi (Electronic Journal of Education, Social Economics and Technology, 2022)
The study examined the awareness of students and use of e-library in tertiary institutions in Ekiti State. Descriptive design of the survey was employed. The population comprised all 100 level and 200 level students in tertiary institutions in Ekiti State while the sample consisted of 150 students drawn from three tertiary institutions in Ekiti State using proportionate sampling techniques. A self-constructed questionnaire titled “Students’ awareness and use of e-library” was used to collect relevant data for the study. The instrument was validated by experienced library expert. A reliability co-efficient of 0.75 was obtained through test re-test method. Data collected were analysed using frequency count and simple percentage. The study revealed that students in tertiary institutions were aware of e-library but with low patronage on the use of electronic database. The major source of awareness of electronic library among the students are through friends and sensitization. The finding revealed that students use youtube page more than online database and  e-journal, e-book and google. Based on the findings, the students should be encouraged to use e-library. Emphasis must be made in the class during the lecture on the use of e-library.